Tensile Properties of Aluminium/Graphite Composite Through Simulation Analysis - Norashidi, Fatin Syahira; Adzila, Sharifah (Journal of Advanced Mechanical Engineering Applications, 2023)
Composite materials are manufactured by the combination of two or more distinct materials. The different materials form the distinct characteristics of the composites. Solid and stiff reinforcement is often inserted into a ductile matrix in aluminium-reinforced composites, which aim to increase mechanical properties, particularly strength, strength-to-weight ratio etc. This research study was focused on detail around the preparation data and tensile properties of Al/Gr composites through simulation analysis. The mixtures of this composite with differ by weight percentages of Gr as reinforcement and with different types of samples were completed shows the differences by its tensile properties. Various weight percentage of Al/Gr composite which were (90/10, 80/20, 60/40). By conducting through this simulation analysis, it is found that when the value of weight percentages is different, the tensile properties will different either based on the strength. In recent years, conventional materials are replaced in most areas with composite materials of aluminium matrix. There are various mechanical studies and analysis that have been done such as, tensile, impact by displacement, and hardness. This simulation analysis have been performed through simulation software that have many features and capable to run testing, which is ANSYS workbench. Moreover, the design of the different types of samples are drawn by using SolidWorks 2019. Then the results of Al/Gr composites are compared for tensile properties.